The Effect of a combination of 12% spirulina and 20% chitosan on macrophage, PMN, and lymphocyte cell expressions in post extraction wound - Nike Hendrijantini; Rostiny Rostiny; Mefina Kuntjoro; Kevin Young; Bunga Shafira; Yunita Pratiwi (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Tooth extraction is the ultimate treatment option for defective teeth followed by the need for dentures. Inflammation is one phase of the healing process that should be minimized in order to preserve alveolar bone for denture support. Macrophage, PMN and lymphocyte cells are indicators of acute inflammation. Spirulina and chitosan are natural compounds with the potential to be anti-inflammatory agents. Purpose: This research aimed to determine macrophage, PMN and lymphocyte cells of animal models treated with a combination of 12% spirulina and 20% chitosan on the 1st, 2nd and 3rd post-extraction day. Methods: Animal models were randomly divided into control (K) and treatment (P) groups. Each group was further divided into three subgroups (KI, KII, KIII and PI, PII, PIII). The post-extraction sockets of the control group animals were then filled with CMC Na 3%. Meanwhile, the post-extraction sockets of the treatment group members were filled with a combination of 12% spirulina and 20% chitosan. Subsequently, the number of PMN, macrophage and lymphocyte cells was analyzed by means of HE analysis on the 1st., 2nd. and 3rd. days. Statistical analysis was then performed using a T-test. Results: There was a decrease in PMN cells and an increase in macrophage and lymphocyte cells on Days 1, 2, and 3. Conclusion: It can be concluded that a combination of 12% spirulina and 20% chitosan can not only decrease PMN cells, but can also increase macrophage and lymphocyte cells on Days 1, 2 and 3 after tooth extraction.